An Investigation of the Role of Sequencing in Children's Reading Comprehension - Gouldthorp, Bethanie; Katsipis, Lia; Mueller, Cara (Reading research quarterly, 2018)
To date, little is known about the high-level language skills and cognitive processes underlying reading comprehension in children. The present study aimed to investigate whether children with high, compared with low, reading comprehension differ in their sequencing skill, which was defined as the ability to identify and recall the temporal order of events in narratives. A novel age-appropriate reading and recall measure was developed to assess sequencing in typically developing primary school students. Sixty-four students between the ages of 8 and 11 years read short narratives containing either a forward or backward temporal shift and then placed a set of cards depicting the scenario in either picture or text format in the correct chronological order that the events occurred. Participants also completed measures of verbal and visuospatial working memory to investigate potential relations between working memory and sequencing ability. High comprehenders were found to produce more accurate sequences than low comprehenders in all conditions of the sequencing task, suggesting that sequencing ability may be important for facilitating comprehension. Additionally, participants produced more accurate sequences in the forward condition than the backward condition, indicating that sequencing is facilitated by chronological presentation of events in text. Measures of working memory were unrelated to sequencing ability or comprehension. The results of this study provide preliminary evidence that sequencing is an important skill for children's comprehension of narrative texts and have implications for reading education and intervention programs.